"We may all soon be 'first-class men'": Gender and Skill in Canada's early twentieth century urban telegraph industry - Tillotson, Shirley (Labour/Le Travailleur, 1991)
Abstract Urban telegraph offices in the early twentieth century employed both women and men as telegraph operators. The fact that both sexes worked together in this skilled occupation makes telegraphy an interesting case for the study of links between gender and skill. Through an examination of the labour process and the telegraph operators' craft culture, this paper describes how the connection between masculinity and skill was established. It is suggested that, while Morse operating provided conditions in which that link was questioned, technological change during World War I helped create a more exaggerated gender division of labour and a newly-defined, fortified link between masculinity and ability